How Standards Solve the Problems of Supply Chain Disintegration for Interdependent Technologies - Owen, Lucas (My University, 2025)
Why do firms coordinate to create technology standards? While prior scholars have largely focused on the role of technology standards in facilitating interoperability to enhance network effects, none have focused on the role of standards in coordinating and diffusing co-specific innovation. From this perspective, interoperability standards address two tiers of a nested problem of asset co-specificity. At the component stage, modularity erodes asset specificity in supply chains and networks. At the standard creation stage, the contractual obligations embedded in technology standards limit opportunism between contributors, allowing them to create co-specific intellectual property without fear of hold-up. I demonstrate this logic with a formal model, and explore nuances and implications in case studies of Nvidia and Apple. I also evaluate robust empirical evidence. Using a difference-in-differences design, I find that standards tend to greatly reduce litigation over standard-essential intellectual property. Finally, I attempt to adjudicate between theories of merit-based idea selection and rent-seeking in standard setting processes and in SEP declarations. While results on idea selection are inconclusive on both sides, evidence suggests that SEP declarations are based on merit and heuristics, and are not driven by rent-seeking.
Thesis (Ph.D.)--University of Washington, 2025
Keywords: 5G; industrial revolution; network; standard; technology; telecommunications; Economics; Political science; Economic history; Political science